A Study on Perception and Exposure to Occupational Risks at Public School Food Services in Bahia, Brazil - Ferreira, Jeane dos Santos; Araújo, Maria da Purificação Nazaré; Botelho, Raquel Braz Assunção; Zandonadi, Renata Puppin; Nakano, Eduardo Yoshio; Raposo, António; Han, Heesup; Muñoz, Marcelo Arraño; Ariza-Montes, Antonio; Akutsu, Rita de Cássia Coelho de Almeida (Frontiers in Public Health, 2022)
Food service work is hazardous due to the intense rhythm of food production, and the working conditions can cause discomfort, fatigue, and occupational accidents and illnesses. For the perception of exposure to occupational hazards, workers must participate in continuing education programs. This study aimed to verify the perception and exposure to occupational risks at school food services (SFS) in Bahia, Brazil. This cross-sectional study was conducted in SFS from public schools in Bahia/Brazil. Researchers identified sociodemographic variables, occupational characteristics, and the Perception of Exposure to Occupational Risks by SFS food handlers. Also, anthropometric assessment (weight, height, and waist circumference), the presence of comorbidities, and the identification of exposure to occupational risks and measures of environmental comfort were evaluated. Most workers were female (98.6%; n = 140), mean age of 46.85 y/o, working as SFS food handlers between one and five years (50.7%; n = 72) but with no training on occupational risks (52.8%; n = 75). This lack of training is not associated with demographic or other occupational variables. The majority of the food handlers present a fair or good perception of exposure to occupational risk. These food handlers are also mostly overweight, and higher BMI was associated with hypertension and edema. The SFS were classified as of high occupational risk (mean of 31.24% of adequacy) environments. Ergonomic Risks had the lowest percentage of adequacy (7.69%, very high risk) regarding occupational risks, followed by chemical risks (31.5% of adequacy, high risk), accident risk (32.19%, high risk), and physical risk (36.89%, high risk). The excess of activities associated with precarious physical structure, insufficient number of equipment and utensils (in inadequate conservation) favors the exposure to occupational risk in SFS.